Clinical applications of cone beam computed tomography in endodontics: literature review (Research, Society and Development, 2022)
In endodontics, imaging is essential during all stages of treatment. In this sense, radiographic examination and cone beam computed tomography (CBCT) are complementary methods used in the diagnosis and planning of endodontic treatment. With the advent of CBCT in endodontic therapy, as it is an exam that uses radiation and allows the reproduction of a section of the human body in any of the three planes of space, that is, in three dimensions (3D), with a minimum distortion and significantly reduced radiation dose compared to fan beam computed tomography (traditional), allowing a greater understanding of anatomy and measurement with tissue destruction by periradicular pathologies. Thus, this study aims to analyze the use of cone beam computed tomography in endodontic treatment, considering its importance in clinical applicability to provide a better diagnosis, planning, prognosis, advantages, disadvantages, limitations and contraindications. Thus, CBCT emerges as a technology that has been approaching the dentist, and overcoming the radiographic limitations during the operative steps. The research was developed through a literature review of literature between the years 2006 to 2021, consulted in the databases of SciELO (Scientific Electronic Library Online), PubMed and LILACS (Latin American and Caribbean Literature in Health Sciences).